2011
DOI: 10.1037/a0022007
|View full text |Cite
|
Sign up to set email alerts
|

Do individual coping strategies help or harm in the work–family conflict situation? Examining coping as a moderator between work–family conflict and well-being.

Abstract: this study we examined the moderator role of coping (problem-, emotion-, and avoidance-focused coping strategies) between work-to-family and family-to-work conflict and well-being (work engagement, job satisfaction, and family satisfaction). The study was based on a sample of 527 Finnish workers. Hierarchical moderated regression analyses showed that emotion-focused coping buffered against job dissatisfaction in a high family-to-work conflict situation. On the other hand, emotionfocused coping was harmful for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 78 publications
4
37
0
1
Order By: Relevance
“…In a very recent empirical study about the stability of coping strategies and patterns, Nielsen and Knardahl (2014) found that self-blame, behavioral disengagement, substance use and denial increased the levels of psychological distress, while active coping, use of instrumental and emotional support, planning, positive reframing and acceptance decreases psychological distress. Similarly, problem-focused coping (planning, decision making and task oriented actions), tends to be associated with positive effects (Folkman & Moskowitz, 2004), while emotional-focused coping lessened work-related wellbeing (Rantanen, Mauno, Kinnunen & Rantanen, 2011) and is associated with poor mental health (Penley, Tomaka & Wiebe, 2002). However, the adaptive qualities of coping processes also need to be evaluated in the specific context in which they occur.…”
Section: Work-family Coping Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent empirical study about the stability of coping strategies and patterns, Nielsen and Knardahl (2014) found that self-blame, behavioral disengagement, substance use and denial increased the levels of psychological distress, while active coping, use of instrumental and emotional support, planning, positive reframing and acceptance decreases psychological distress. Similarly, problem-focused coping (planning, decision making and task oriented actions), tends to be associated with positive effects (Folkman & Moskowitz, 2004), while emotional-focused coping lessened work-related wellbeing (Rantanen, Mauno, Kinnunen & Rantanen, 2011) and is associated with poor mental health (Penley, Tomaka & Wiebe, 2002). However, the adaptive qualities of coping processes also need to be evaluated in the specific context in which they occur.…”
Section: Work-family Coping Effectivenessmentioning
confidence: 99%
“…An explanation proposed to this lack of association is that problem focused coping is more adaptive when situations are amenable to change. In fact, individuals may have a greater control and opportunity for positive change in the family domain than in the work environment (Rantanen et al, 2011;Rotondo & Kincaid, 2008), as work environments are less tolerant of change for the purpose of accommodating family needs (Rotondo & Kincaid, 2008). Indeed, coping with role overload by restructuring family roles was a more manageable strategy to reduce stress than restructuring work roles (Higgins, Duxbury & Lyons, 2010).…”
Section: Work-family Coping Effectivenessmentioning
confidence: 99%
“…Consistent with this proposition, Lazarus (1993) suggested that avoidance coping might actually be facilitative, and empirical research has demonstrated that avoidance coping can be adaptive (Cohen, Evans, Stokols, & Krantz, 1986). Further, avoidance coping has been found to buffer the effects of role conflict and role overload, and lead to higher levels of satisfaction (Rantanen et al, 2011). We propose:…”
Section: Avoidance Copingmentioning
confidence: 69%
“…Research indicates that direct action coping strategies have positive effects on work-life conflict (Rotondo & Kincaid, 2008), venting has negative effects on work-life conflict (Andreassi, 2011), and positive thinking has no effect on work-life conflict (Haar, 2006). A handful of studies have also examined avoidance coping and yielded mixed findings-some have found that it is detrimental (Andreassi, 2011;Haar, 2006;Rotondo et al, 2003), although others have found it to be beneficial (Hecht & McCarthy, 2010;Innstrand, Langballe, Espnes, Falkum, & Aasland, 2008;Paden & Buehler, 1995;Rantanen, Mauno, Kinnunen, & Rantanen, 2011).…”
Section: Avoidance Copingmentioning
confidence: 99%
“…The existing (albeit limited) research that addresses individual-level strategies for managing multiple life roles focusses almost exclusively on coping with work-family conflict (e.g. Baltes et al, 2011;Rantanen et al, 2011;Somech and Drach-Zahavy, 2012). However, such research rarely explores the extent to which such strategies are trainable and, if so, the effectiveness of work-place interventions .…”
mentioning
confidence: 99%